Mechanical Properties Damage, Fracture Evolution, and Constitutive Model of Siltstone under the Effect of Moisture Content - Weinan Wang; Qiangling Yao; Chuanjin Tang; Haitao Li; Hengyi Liu; Changhao Shan (Geofluids)
In order to study the weakening mechanism of mechanical properties and the evolution of fracture of water-bearing rocks, cylindrical standard siltstone samples with four moisture contents (0, 2.85, 3.87, and 4.25%) were prepared, and the mechanical properties, damage mode, AE characteristics, and fractal law of water-bearing rock samples were studied by means of uniaxial compression test and acoustic emission (AE) monitoring technique, and based on the test findings, a constitutive model of the entire process of rock deformation and damage under uniaxial compression was built with different moisture content of rock. The results show that with the increase of moisture content, the peak stress, the stress threshold of void compaction stage, and the stress threshold of elastic stage of the rock samples decreased linearly, elastic modulus decreased exponentially as a function, and the peak strain, the strain threshold of void compaction stage, and the strain threshold of elastic stage increased linearly. The higher the moisture content, the weaker the AE signal intensity and the smaller the AE count value. From dry to saturated, the damage form of rock samples gradually transitioned from predominantly tensile damage to predominantly shear damage. The fractal dimension of the broken block linearly decreases as the moisture content rises. The model constructed in this paper has good applicability to the deformation characteristics of water-bearing rocks under uniaxial compression before the peak stress; it especially can express the rock void compaction stage, but it cannot accurately describe the postpeak deformation characteristics.